Reforming India's higher civil services: Agenda for 21st century reforms - Fadia, Kuldeep (2014)
The ramifications of global changes are being felt by the government in the form of increasing citizen expectations for better governance through effective service delivery, transparency, accountability and rule of law. The civil service, as the prime constituent of government, must keep pace with the changing ties in order to meet the aspirations of the people. The purpose of reform is to reorient the civil services into a dynamic, efficient and accountable apparatus for public service delivery built on the public service ethos and values of integrity, equity and neutrality. - Reproduced.
Keywords: Administrative reform - India; Civil service - india; Civil service